2005
DOI: 10.1158/0008-5472.can-04-3858
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Activity of Src Regulate Interleukin-8 Expression in Pancreatic Adenocarcinoma Cells: Implications for Angiogenesis

Abstract: Interleukin-8 (IL-8) is an angiogenic factor that promotes growth of pancreatic tumors. The purpose of this study was to determine if c-Src, a protein tyrosine kinase frequently overexpressed in pancreatic cancer, regulated IL-8 expression and to elucidate the Src-mediated signaling pathways that contribute to angiogenesis in pancreatic adenocarcinoma cells. In a panel of pancreatic cancer cell lines, expression of total and activated Src correlated with IL-8 production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 40 publications
3
68
0
Order By: Relevance
“…3B). By using an inhibitor of phospho-p38 (SB 203580) (26) (Fig. S6A), an increase in CBP/p300 expression is seen in NT-transduced cell lines, demonstrating that p38 inhibits CBP/p300 ( Fig.…”
Section: Par-1 Regulates Binding Of Ets-1 and C-jun To The Maspin Promentioning
confidence: 94%
“…3B). By using an inhibitor of phospho-p38 (SB 203580) (26) (Fig. S6A), an increase in CBP/p300 expression is seen in NT-transduced cell lines, demonstrating that p38 inhibits CBP/p300 ( Fig.…”
Section: Par-1 Regulates Binding Of Ets-1 and C-jun To The Maspin Promentioning
confidence: 94%
“…siRNA expression plasmids were created as described elsewhere, 13 using the Ambion pSilencer 1.0-U6 (Austin, TX) according to manufacturer's directions. Briefly, c-Srcspecific target sequences were designed using the Ambion siRNA Web design tool.…”
Section: Creation Of Small Interfering Rna (Sirna) Expression Plasmidmentioning
confidence: 99%
“…We have recently demonstrated that Src is a critical regulator of pro-angiogenic molecules. [13][14][15] Duxbury et al 16 have provided evidence that gemcitabine resistance correlates with increased Src activity, and Src inhibition overcomes this resistance. Recently, Src inhibition with a novel Src family kinase inhibitor has demonstrated significant antitumor and antimetastatic activity in a pancreatic cancer orthotopic nude mouse model.…”
mentioning
confidence: 99%
“…The role of proinflammatory cytokines in tumour progression, angiogenesis and metastases has been elucidated in recent years. Specifically, IL-8 was shown to be a potent proangiogenic factor associated with increased microvessel count, increased VEGF expression and poor prognosis in oesophageal squamous cell carcinoma, colonic cancer cells and pancreatic adenocarcinoma cells (Mizukami et al, 2005;Ren et al, 2005;Trevino et al, 2005). Various studies have shown that blocking IL-8 expression reversed many of these proangiogenic and metastatic cell activities, further supporting the important role of this proinflammatory cytokine in tumour progression ((Mizukami et al, 2005;Ren et al, 2005;Trevino et al, 2005).…”
mentioning
confidence: 96%